2009
DOI: 10.1111/j.1467-8691.2009.00519.x
|View full text |Cite
|
Sign up to set email alerts
|

Capabilities and Radical Changes of the Business Models of New Bioscience Firms

Abstract: The paper analyses the development of newly started bioscience firms in terms of their capabilities and changes in their business models. The study consists of eight retrospective case studies stemming from their foundation over a period of 5-15 years. Empirically the paper finds that all the firms quickly develop a technological capability at the time of their foundation, and over time all firms added distinctly new business capabilities. Seven firms radically changed their business models by identifying and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 52 publications
(56 reference statements)
0
33
0
1
Order By: Relevance
“…Analytical applications of the business model innovation concept involve analysis of the extent to which different constituents of business models are affected by the introduction of new technologies. Instances of such analysis involve 3D printing (Rayna & Striukova, 2016), bioscience innovations (Brink & Holmén, 2009) or cloud technologies (DaSilva, Trkman, Desouza, & Lindič, 2013). Overall, the literature indicates endogenous and exogenous sources of business model innovation.…”
Section: Literature Review -Business Modelsmentioning
confidence: 99%
“…Analytical applications of the business model innovation concept involve analysis of the extent to which different constituents of business models are affected by the introduction of new technologies. Instances of such analysis involve 3D printing (Rayna & Striukova, 2016), bioscience innovations (Brink & Holmén, 2009) or cloud technologies (DaSilva, Trkman, Desouza, & Lindič, 2013). Overall, the literature indicates endogenous and exogenous sources of business model innovation.…”
Section: Literature Review -Business Modelsmentioning
confidence: 99%
“…108,109 Business Models Change Dynamics are 4 publications focused on the dynamics of why biopharmaceutical firms change their business model over time. These dynamics include new commercial opportunity recognition 110 , the opportunity to capture more value from their discovery efforts by expanding toward therapy development 111 or even a natural evolutionary trend toward therapy development after founding due to resource constraints.…”
Section: 93 Drivers Of Business Model Choicementioning
confidence: 99%
“…Brink and Holmén (2009) longitudinally explored the association between the evolution of the firm's set of capabilities and changes in their business models in the bioscience industry and concluded that the lack of certain technological capabilities is not an obstacle for firms to change and adopt a business model, rather the existence (or absence) of business-related capabilities hinders the change.…”
Section: Key Aspects Of Business Model Changementioning
confidence: 99%
“…Questions on the frequency and radicalness of business model change (Brink & Holmén, 2009), factors driving the evolution of successful business models (George & Bock, 2011) and the nature of the dynamic forces shaping business models over time (Zott & Amit, 2013) are motivations for an exploratory, quantitative and longitudinal view of a process that has been historically approached from a static stance (Demil & Lecocq, 2010).…”
Section: Research Orientation and Typementioning
confidence: 99%
See 1 more Smart Citation